(untitled) (Delta Medical College Journal, 2020)
COVID-19 pandemic has brought about many challenges in dental practice for dental professionals and their team. The route of transmission of the virus and the nature of dental service has put dental professionals at risk of being exposed and infected by the virus and at the same time making dentistry itself a part of the infectious chain of COVID-19. The World Health Organization (WHO) has advised dental professionals across the world to limit dental practice to emergency cases only and postpone all non-essential dental services. According to Bangladesh Dental Society, about 10,000 practicing dentists and near about 20,000 supporting staff are involved in dental health practice in the country. There are about 4,000 dental clinics only in Dhaka city. A dental practice guideline has been developed by Bangladesh Dental Society to employ by dental professionals during COVID-19 pandemic. However, we feel that efforts to explore the real scenario of proper safety precaution and maintenance of public health measures in COVID-19 is less evident in the manuals in the context of public health and patient safety in Bangladesh. Hence, we proposed this review paper through an extensive literature and guidelines search to explore the risks of COVID-19 transmission inside dental settings, explore recommended safety protocols to minimize those risks and address the challenges associated with resuming regular dental and oral health practice. Delta Med Col J. Jul 2020;8(2): 93-100